Polygon Shape Formation for Multi-Mobile Robots in a Local Knowledge Environment - Rashid, Abdulmuttalib T.; Ali, Abduladhem A. (Basrah Journal for Engineering Sciences, 2019)
Formation control is a critical task in the coordination of multi-mobile robot systems operating in structured environments with limited local knowledge and low-cost hardware. Achieving reliable formations requires effective localization, path planning, and obstacle avoidance capabilities. This study presents a static strategy for forming polygon-shaped configurations using multiple mobile robots. The proposed strategy improves formation efficiency by employing a cluster matching algorithm instead of the conventional triangulation approach to complete the formation process. In addition, the visibility binary tree algorithm and the reciprocal orientation algorithm are integrated to enhance robot coordination and spatial awareness. Simulation results demonstrate that the proposed strategy achieves superior performance in multi-robot formation tasks, offering improved efficiency and robustness compared with traditional triangulation-based methods.